Chapter 11 - Hydrogen energy–Potential in developing countries - Monir, Minhaj Uddin; Azrina, Abd Aziz; Ahmed, Mohammad Tofayal; Hasan, Md. Yeasir (Elsevier, 2022)
Energy is essential for human life, societal civilization, and economic growth. Hydrogen energy has emerged as an important component of global energy policies and frameworks, especially in developed countries. This chapter discusses the potential for hydrogen energy in relation to hydrogen production in developing countries. The subsequent sections elaborate on the different sources of hydrogen production, technologies for processing paths, including thermal, electrolytic, photolytic, and fermentation processes. This chapter also focuses on the current and future challenges of hydrogen conversion to electricity. The extraction of hydrogen from renewable and nonrenewable sources presents an appealing potential to realize the maximum environmental value of hydrogen as an electricity carrier. Therefore, the purpose of this chapter is to provide the hydrogen production technologies followed by its present adoption status and future prospect in the developing economies.